Correlation of Pre-Operative CA-125 with Clinico-histological Characteristics in Ovarian Tumor Cases (The Planet, 2024)
Introduction: The clinical presentations of ovarian tumors are non-specific. The measurement of CA-125 levels, often combined with other modalities such as bimanual pelvic examination and transvaginal ultrasonography, is suggested for early detection of ovarian cancer—a key application of this tumor marker. Aim of the study: This study aimed to assess the correlation of pre-operative CA-125 with clinico-histological characteristics in ovarian tumor cases. Methods and materials: This cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Combined Military Hospital, Dhaka, Bangladesh from July 2016 to January 2017. As the study subjects, a total of 100 cases presenting with ovarian tumors were enrolled using a convenience sampling technique. Data analysis was performed using MS Office tools and SPSS Version 23.0. Results: Histological analysis in this study revealed a predominance of benign tumors (58%) over malignant tumors (42%). Among women with benign ovarian tumors, 79.3% had CA 125 levels ≤35 U/ml, whereas in malignant ovarian tumors, 95.2% had levels >35 U/ml (p
Keywords: Preoperative CA-125; Ovarian tumor; Malignant; Menopause; Tumor